Central serotonin-2A (5-HT2A) receptor dysfunction in depression and epilepsy: the missing link? - Guiard, Bruno P.; Giovanni, Giuseppe Di (Frontiers in Pharmacology, 2015)
5-Hydroxytryptamine 2A receptors (5-HT2A-Rs) are G-protein coupled receptors. In agreement with their location in the brain, they have been implicated not only in various central physiological functions including memory, sleep, nociception, eating and reward behaviors, but also in many neuropsychiatric disorders. Interestingly, a bidirectional link between depression and epilepsy is suspected since patients with depression and especially suicide attempters have an increased seizure risk, while a significant percentage of epileptic patients suffer from depression. Such epidemiological data led us to hypothesize that both pathologies may share common anatomical and neurobiological alteration of the 5-HT2A signaling. After a brief presentation of the pharmacological properties of the 5-HT2A-Rs, this review illustrates how these receptors may directly or indirectly control neuronal excitability in most networks involved in depression and epilepsy through interactions with the monoaminergic, GABAergic and glutamatergic neurotransmissions. It also synthetizes the preclinical and clinical evidence demonstrating the role of these receptors in antidepressant and antiepileptic responses.